Dynamic characteristics of the light emission, accompanying the cryocondensation of some gases - Drobyshev, A.; Aldiyarov, A.; Kurnosov, V.; Korshikov, E.; Sokolov, D.; Galitskaya, Y.; Kozhamkulov, T. (Хабаршы. Физика сериясы, 2015)
Processes of thin films cryovacuum condensates of different gases, as well as their properties are the object of attention of researchers for more than a decade. Previously, we conducted studies in which it was found interesting behavior of nitrous oxide in the process of condensation and thermal cycling of the condensed sample.